(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article addresses the perception and comprehension of Russian phraseology within the contexts of artificial and natural bilingualism in Uzbekistan. We conducted a comparative analysis of the phraseological corpus, identifying types of interlinguistic equivalence and determining the proportion of non-equivalent units within Uzbekistani school curricula (textbooks for grades 4–6). The article presents the results of an experimental study that identified typical errors in idiom interpretation, such as literal decoding and a lack of background knowledge. Particular attention is paid to the "cultural component" as a primary factor determining language acquisition difficulties. The study demonstrates a direct correlation between the intensity of the linguistic environment and the depth of understanding regarding the figurative structure of speech.